2008
DOI: 10.1111/j.1572-0241.2007.01561.x
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Work Disability in Crohn's Disease

Abstract: Permanent work disability administered through social security was encountered in 5.3% of the Crohn's patients followed in our cohort. Patients who consistently report low quality of life, or have frequent flares requiring surgical intervention or hospitalization for medical management, may be at risk for CD-related work disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 8 publications
7
65
2
2
Order By: Relevance
“…Furthermore, females have greater disease-related concerns and worries about being treated differently as a result of their disease (31) and are also more likely to report concerns related to attractiveness and body image (8,28) . Previous studies have shown that HRQOL is significantly impaired by work disability (2,3,17,42) . The work disability rates of IBD patients range between 1.3% and 34% (45) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, females have greater disease-related concerns and worries about being treated differently as a result of their disease (31) and are also more likely to report concerns related to attractiveness and body image (8,28) . Previous studies have shown that HRQOL is significantly impaired by work disability (2,3,17,42) . The work disability rates of IBD patients range between 1.3% and 34% (45) .…”
Section: Discussionmentioning
confidence: 99%
“…The work disability rates of IBD patients range between 1.3% and 34% (45) . The frequent flares requiring hospitalization or surgical intervention often leads to sick leave and disability pensions (2,3,4,6,20,44) , which may be the main reason for the decreased career fulfillment in IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 We examined the use of concomitant immunosuppressive medications including azathioprine, 6-mercaptopurine, and methotrexate. Disease behavior was characterized according to the Montreal Classification as inflammatory, stricturing, or fistulizing disease.…”
Section: Variablesmentioning
confidence: 99%
“…13,14 In addition to these direct health costs, another important indirect economic consequence of this chronic illness in an economically productive age-group is the cost attributable to lost work productivity and permanent work disability. [15][16][17][18] Hence, measuring the long-term performance of CD drug therapy in routine clinical care needs to emphasize prevention of these CD-related complications. Evaluation of long-term use of infliximab in the routine clinical setting beyond 1 year and its ability to decrease these CD-related complications has been limited to date.…”
mentioning
confidence: 99%
“…By hand searching, only 9 out of 16 papers published in the English language were found to cover disability in CD. Overall, work is the only dimension of disability that has been widely assessed in IBD [18] . When compared to other disabling diseases, such as multiple sclerosis and rheumatoid arthritis, the consequences of impaired functions (disability) on the management of IBD have been clearly un derestimated.…”
Section: A Need To Develop the First Disability Index For Ibdmentioning
confidence: 99%